China sustainable homebuilding - Renouf, Daniel; Clech, Patrice (New Jersey : Films for the Humanities & Sciences [distributor], 2009)
In order to reduce China's carbon footprint, the Chinese construction industry has developed and implemented new homebuilding standards.
Camera, David Alexandre; programme editors, Nadia Gillet, Marina Pok; journalist, Sophie Thomas Gerard; editing, Adrien Gemonet; dubbing, Cyrille Soulas.
Keywords: Sustainable buildings -- Design and construction -- Standards -- China; Dwellings -- Environmental engineering -- China; Architecture and energy conservation -- China